Redesain Pasar Pagi Jalan HR. Soebrantas Pekanbaru Dengan Pendekatan Arsitektur Tropis - Asmadi Asmadi; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Pasar Pagi located in HR.Soebrantas street takes an imfortant role in fulfilling the needs of the society surroundings, completely to the economic social order. Considering the unsuppported services faced in these public facilities; frequently traffic congestion, insufficient parking space, poor drainage system, and incompletely arranged market spot, redesigning of the Pasar Pagi is a significance to overcome the cases exist. The design method undertaken prior to the project uses the principle of tropical, functional, structural, and esthetical architecture. Since the interactions within the community of the Pasar Pagi are various, those activities developed should meet the standard quality in accordance with the Presidential Decree Republic of Indonesia No. 112 year 2007; traditionally market inside and outside ordering based, well-facilitated principle and responsibly designed tropical architecture. Keywords: Pasar Pagi, tropical architecture, redesign.